Wuweizisu C from Schisandra chinensis decreases membrane potential in C6 glioma cells - Choi Young-whan; Kim Kyeok; Jo Ji-yeong; Kim Hyo-lim; Lee You-jin; Shin Woo-jung; Sacket Santosh J; Han Mijin; Im Dong-soon (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of dibenzocyclooctadiene lignans isolated from Schisandra chinensis, such as wuweizisu C, gomisin N, gomisin A, and schisandrin, on the membrane potential in C6 glioma cells. Methods: The membrane potential was estimated by measuring the fluorescence change in DiBAC-loaded glioma cells. Results: Wuweizisu C decreased the membrane potential in a concentration-dependent manner. Gomisin N and gomisin A, however, showed differential modulation and no change was induced by schisandrin or dimethyl-4,4′-dimethoxy-5,6,5′,6′-dimethylene dioxybipheny 1-2,2′-dicarboxylate, a synthetic drug derived from dibenzocyclooctadiene lignans. We found no involvement of Gi/o proteins, phospholipase C, and extracellular Na+ on the wuweizisu C-induced decrease of the membrane potential. Wuweizisu C by itself did not change the intracellular Ca2+ [Ca2+]i concentration, but decreased the ATP-indu-ced Ca2+ increase in C6 glioma cells. The 4 lignans at all concentrations used in this study did not induce any effect on cell viability. Furthermore, we found a similar decrease of the membrane potential by wuweizisu C in PC12 neuronal cells. Conclusion: Our results suggest that the decrease in the membrane potential and the modulation of [Ca2+]i concentration by wuweizisu C could be important action mechanisms of wuweizisu C.